1997
DOI: 10.1097/00007632-199704150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Lumbar Medial Branch and L5 Dorsal Ramus Blocks

Abstract: When the appropriate technique is used, medial branch blocks are target specific. To guard against false-negative responses due to intravenous up-take, contrast medium must be used before the injection of local anaesthetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
175
1
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(185 citation statements)
references
References 11 publications
0
175
1
9
Order By: Relevance
“…The facet joint(s) may be diagnosed as the source of pain either by intra-articular injection of the facet joint(s) with local anaesthetic or by local anaesthetic block injection to the medial branches of the posterior primary rami, which are the sole sensory nerve supply from the facet joints. 10 Each joint receives innervation from two medial branches (at the level of the facet joint and the level above) and so both branches need to be blocked to diagnose facet joint pain (Figure 1,A,B). 11 The sacroiliac joint may be diagnosed similarly by intra-articular injection of local anaesthetic but as the sensory nerve supply is variable it is not feasible to diagnose through nerve blockade (Figure 1,C).…”
Section: Introductionmentioning
confidence: 99%
“…The facet joint(s) may be diagnosed as the source of pain either by intra-articular injection of the facet joint(s) with local anaesthetic or by local anaesthetic block injection to the medial branches of the posterior primary rami, which are the sole sensory nerve supply from the facet joints. 10 Each joint receives innervation from two medial branches (at the level of the facet joint and the level above) and so both branches need to be blocked to diagnose facet joint pain (Figure 1,A,B). 11 The sacroiliac joint may be diagnosed similarly by intra-articular injection of local anaesthetic but as the sensory nerve supply is variable it is not feasible to diagnose through nerve blockade (Figure 1,C).…”
Section: Introductionmentioning
confidence: 99%
“…After identifying the target beads, to see the transverse and superior articular processes (SAP) and to obtain a view of the cross shaft became ultrasound probe to 90 degrees to show the distance from the cephalad margin of the adjacent groove side to the SAP (16), and the nearest skin surface was measured using an ultrasound caliper. Local anesthesia was performed with a 1% lidocaine injection (1 mL).…”
Section: Methodsmentioning
confidence: 99%
“…Medial branch also innervates the multifidus, interspinales, and intertransversarii mediales muscles, JORAPAIN the interspinous ligament, and, possibly, the ligamentum flavum. 4 Histological studies have shown that capsules of the facet joints are richly innervated with free nerve endings. This means that they are endowed with the appropriate sensory apparatus to transmit proprio ceptive and nociceptive information.…”
Section: Anatomymentioning
confidence: 99%